Students in the information environment: a study of educational and extracurricular activities. (2015) - Noskova, Tatiana; Yakovleva, Olga; Pavlova, Tatiana; Smyrnova-Trybulska, Eugenia
The development of the global world makes it necessary to conduct international studies of students' educational and extracurricular activities. This article describes several research directions pursued at Herzen State Pedagogical University of Russia (HSPU), Saint-Petersburg and University of Silesia (US), Poland as well as research directions and outcomes within the European IRNet Project (http://www.irnet.us.edu.pl). Firstly, a questionnaire as well as other research tools were developed, implemented and analysed in order to ascertain students' new educational strategies and educational needs. Secondly, in order to understand in what way young people are aware of the surrounding reality a number of online discussions were held with the students and the discourses were analysed. The questionnaire included several research directions: the specifics of students' communication activities in an electronic networked environment; the characteristics of information retrieval activities and the preferences in the choice of particular resources in the network; the attitude towards the information and communication network resources and services used in education, future professional work and self-education.